Long-term operation of solid oxide fuel cells and preliminary findings on accelerated testing. (18th March 2020) - Blum, Ludger; Fang, Qingping; Groß-Barsnick, Sonja M.; de Haart, L.G.J. (Bert); Malzbender, Jürgen; Menzler, Norbert H.; Quadakkers, Willem J.
Abstract: Stationary applications of Solid Oxide Fuel Cell systems require operating times of 40, 000 to 80, 000 h for market introduction. Therefore, extended lifetime tests are essential for learning about the long-term behavior and various degradation mechanisms and to foster ideas about accelerated stack testing. The Forschungszentrum Jülich has been gradually extending the testing time, resulting in successful short-stack operating times of between 20, 000 and 40, 000 h. This work highlights the results of these long-term tests and compares the observations for different material combinations, operating temperatures of 700 and 800 °C, including different fuel utilizations and gas compositions. An increase of temperature from 700 to 800 °C leads to an acceleration of the degradation rate by a factor of 1.5–2. Meanwhile, an increase in fuel utilization from 40 to 80% did not result in increased degradation. The same was found for higher current densities of up to 1 Acm −2 . Highlights: Comparison of long-term tests between 20, 000 and 40, 000 h. With a good Cr retention layer, the degradation can be lowered down to <0.3%/kh. Increasing temperature from 700 to 800 °C accelerates degradation by a factor of 1.5–2. High fuel utilization and internal reforming show no significant effect on degradation. Different contact layers or IC materials have no significant effect on degradation.